2012
DOI: 10.1002/adhm.201100039
|View full text |Cite
|
Sign up to set email alerts
|

New Biomimetic Directions in Regenerative Ophthalmology

Abstract: One of the most complete and permanent ways of treating many causes of visual impairment and blindness is to replace the entire affected tissue with pre-cultured ocular tissues supported and maintained on biomaterial frameworks. One direction towards enhancing ocular tissue regeneration on biomaterials, in the laboratory is by applying biomimicry. Specifically to engineer biomaterials with important functional elements of the native extracellular matrices, such as topography, that support and organise cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 88 publications
0
13
0
Order By: Relevance
“…Introduction 54 Nature has provided scientists through the process of evolution 55 with a diverse range of micro/nanostructures which are a poten- 56 tially rich blueprint for new technologies and materials [1][2][3][4][5]. 57 These 'free' architectural adaptations are of particular interest in 58 relation to surfaces as control of interfacial properties is a key 59 aspect in many current and emerging industries. While the 60 epidermis of many organisms (plants and animals) has been exam- has been shown or speculated to exhibit a range of functions 79 including acdyiss, coping with varying temperatures, pheromone 80 capture, retention, and dispersal, tribological functions such as 81 reduction of friction and wear protection and also reflection of 82 radiation.…”
mentioning
confidence: 99%
“…Introduction 54 Nature has provided scientists through the process of evolution 55 with a diverse range of micro/nanostructures which are a poten- 56 tially rich blueprint for new technologies and materials [1][2][3][4][5]. 57 These 'free' architectural adaptations are of particular interest in 58 relation to surfaces as control of interfacial properties is a key 59 aspect in many current and emerging industries. While the 60 epidermis of many organisms (plants and animals) has been exam- has been shown or speculated to exhibit a range of functions 79 including acdyiss, coping with varying temperatures, pheromone 80 capture, retention, and dispersal, tribological functions such as 81 reduction of friction and wear protection and also reflection of 82 radiation.…”
mentioning
confidence: 99%
“…We are looking at exploiting those products that have previously evolved in early and simple life-forms exemplified by marine sponges and planktonic organisms. Ultimate biomimicry is the ability to emulate and simulate human biology [37]. In the meantime, there is a strong case for using natural products of all types in regenerative strategies requiring a framework because of their pre-organization into superior and sophisticated structures.…”
Section: Biomedical Applications Of Marine Productsmentioning
confidence: 99%
“…One interesting origin for discovering usable items with the utility and versatility necessary to complete tissue generation are the products of evolution from simple animals and plants. Previously, we have demonstrated how this has yielded drug delivery devices, cell sheet templates and frameworks for cartilage regeneration [36,37,38,39]. In this article, we look at the possibilities of harnessing structures, substrates and materials from the world of marine biology for use in the tissue engineering of dental tissues, jawbone, dentine and pulp.…”
Section: Introductionmentioning
confidence: 99%
“…[197] Recently, applications of various nano-topographical structures inspired from nature have been proposed also with human retinal pigment epithelial cells for ophthalmic tissue regeneration. [198] To conclude, mimicking the tissue surface nano-features with biomaterials might be a powerful way to handle cellular fate and thus to c chemica surface c precipitat onto the Further m structure designing swell in t structure biocompa bioactive [199,200] mensional ng allows als able to l network ave good and other es.…”
Section: Instructive Factors In Tissuesmentioning
confidence: 99%
“…[180] In mid 1990s it has been shown that almost all mammalian cells respond to the tissue topography activating different cellular behaviors. [181][182][183][184][185][186][187][188][189][190][191][192][193][194][195][196][197][198] For example, various experiments showed that cells adhere onto nano-grates and align along the direction of the grating. When human fibroblasts were seeded on silicon gratings with heights ranging from 50 to 600 nm, they aligned according to the direction of the grooves with an increased response to deeper gratings.…”
Section: Instructive Factors In Tissuesmentioning
confidence: 99%